THE SPATIAL PATTERN OF URBANIZATION AND SMALL CITIES DEVELOPMENT IN CENTRAL JAVA: A CASE STUDY OF SEMARANG-YOGYAKARTA-SURAKARTA REGION - Jawoto Sih Setyono; Hadi Sabari Yunus; Sri Rum Giyarsih (Geoplanning: Journal of Geomatics and Planning, 2016)
The special form of urbanization in Indonesia has led to a variety of themes on the urban development studies in Indonesia. Since 1990s, there has been an emphasis on the development of mega-urban regions, particularly those surrounding Jakarta as the biggest and the prime city in Indonesia. This research is aimed at elaborating the previous knowledge on the urbanization pattern in Indonesia, and Java in particular. More specifically, this study examines urban development trend in Central Java. The analysis of urbanization in this study can be classified into two categories, i.e. analysis of the urbanization level and analysis of the urbanization growth. These two analyses are combined by applying some GIS methods in order to understand the pattern of urbanization in the region. It is found that the urbanization process in Central Java has transformed the predominantly rural regions in the 1980s into the urban ones. The rapid growth of urban population forms some observable pattern that may be different to the national pattern. There are common spatial patterns, such as the importance of the coastal region and the essential role of the larger urban centers in the urbanization. In this regards, the emergence of the smaller centers has also contributed to the process, especially in bridging a more balanced development between major urban centers and their respective rural hinterland.